Effect of Adaptive Compression and Fast-Acting WDRC Strategies on Sentence Recognition in Noise in Mandarin-Speaking Pediatric Hearing Aid Users - Liu, Haihong; Liu, Yuanhu; Li, Ying; Jin, Xin; Li, Jing; Zhou, Yi; Ge, Wentong; Ni, Xin (Journal of the American Academy of Audiology, 2018)
Wide dynamic range compression (WDRC) has been widely used in hearing aid technology. However, several reports indicate that WDRC may improve audibility at the expense of speech intelligibility. As such, a modified amplification compression scheme, named adaptive compression, was developed. However, the effect of compression strategies on speech perception in pediatric hearing aid users has not been clearly reported.The purpose of the present study was to investigate the effect of adaptive compression and fast-acting WDRC processing strategies on sentence recognition in noise with Mandarin, pediatric hearing aid users.This study was set up using a double-blind, within-subject, repeated-measures design.Twenty-six children who spoke Mandarin Chinese as their primary language and had bilateral sensorineural hearing loss participated in the study.Sentence recognition in noise was evaluated in behind-the-ear technology with both adaptive compression processing and fast-acting WDRC processing and was selected randomly for each child. Percent correct sentence recognition in noise with fast-acting WDRC and adaptive compression was collected from each participant. Correlation analysis was performed to examine the effect of gender, age at assessment, and hearing threshold of the better ear on signal-to-noise ratio, and a paired-samples t test was employed to compare the performance of the adaptive compression strategy and fast-acting WDRC processing.The mean percentage correct of sentence recognition in noise with behind-the-ear technology with fast-acting WDRC and adaptive compression processing were 62.24% and 68.71%, respectively. The paired-samples t test showed that the performance of the adaptive compression strategy was significantly better than the fast-acting WDRC processing (t = 3.190, p = 0.004).Compared with the fast-acting WDRC, adaptive compression provided better sentence recognition in noise for Mandarin pediatric hearing aid users.
Keywords: adaptive compression; children; hearing aid; noise; sentence recognition; WDRC